Bibliometric Analysis of Digital Agriculture Research in the Agricultural Sector - Loso Judijanto (Westscience Press, 2026)
The rapid advancement of digital technologies has significantly transformed the agricultural sector, giving rise to the concept of digital agriculture. This study aims to analyze the global development, thematic structure, and collaboration patterns of digital agriculture research through a comprehensive bibliometric approach. Data were retrieved from the Scopus database covering publications from 2010 to 2024 and analyzed using VOSviewer to examine co-authorship networks, country collaboration, keyword co-occurrence, overlay visualization, and density mapping. The results indicate a substantial growth in scholarly output, particularly in recent years, reflecting increasing global attention to agricultural digitalization. Core research themes revolve around digital transformation, artificial intelligence, Internet of Things (IoT), precision agriculture, and sustainable development. Emerging topics such as blockchain, digital platforms, and innovation ecosystems suggest a shift toward integrated and system-level approaches. Country collaboration analysis highlights China, India, and the United States as major contributors, supported by active European research networks. Digital agriculture research has evolved from a technology-centered perspective toward a broader ecosystem-oriented framework integrating sustainability, supply chain digitalization, and innovation. The findings provide a comprehensive overview of the intellectual structure of the field and identify potential directions for future research, particularly in governance, inclusivity, and long-term socio-economic impact.